2020
DOI: 10.1088/1757-899x/747/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Interaction model of one jaw of a vibrating jaw crusher with the processed rock, taking into account the properties of the electric motor

Abstract: Vibratory jaw crushers are modern machines for grinding and rock crushing. Single jaw of vibratory jaw crusher is considered in this paper. Phenomenological model of interaction of the jaw and rock is proposed. Two options for considering the power of an unbalanced drive are considered. In the first, an unbalanced vibrator has a constant angular velocity relative to the bed. In the second, the electromechanical characteristics of the electric motor, which drives the unbalanced vibrator, are taken into account.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Results showed that the main cause of structure failure is fast-growing fatigue cracks formed during operation. A single jaw vibrator with constant angular velocity and unbalanced vibration was studied [23].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the main cause of structure failure is fast-growing fatigue cracks formed during operation. A single jaw vibrator with constant angular velocity and unbalanced vibration was studied [23].…”
Section: Introductionmentioning
confidence: 99%